A recipe for revolution: Could 1968 happen today?. Issue 1 (23rd June 2013) - Gildea, Robert
Abstract : HistorianRobert Gildea looks back at the actions and consequences of 1968, and asks whether modern protest movements have the means and motivation to spark a revolutionary repeat.